CHILDHOOD OBESITY IN THE UNITED STATES OF AMERICA - Aly, Ezzeldin R. (European Scientific Journal, ESJ, 2014)
Obesity in the U.S. is a problem that is beginning to grow large in our children‘s lives. The solution to this problem is centered in three areas; the help of the community, health education, and consumer education. The two main factors casing childhood obesity is eating high fat, high protein foods along with a serious sedentary lifestyle. Childhood obesity in the United State is a rising epidemic, a serious health crisis, and is steadily increasing because it seems that people refuse to change for the good of the nation. Since the last decade the percentage of children being obese has increased steadily. The cause of this is a poor nutrition and physical activity and the plan is to get back to how it used to be, if not better. Children in the U.S. are eating more processed foods at home and there is less physical activity and sports at school. While children are developing bad habits when they are young, they are likely to turn into an adult who is obese and has bad habits. This is a serious issue that needs the attentions of everyone, including government, researchers, media, schools, public health officials, and parents.